Through a prism darkly: re-evaluating prisms and neglect - Striemer, Christopher; Danckert, James (My University, 2010)
Many studies have demonstrated that prism adaptation can reduce several symptoms of visual neglect, a disorder in which patients fail to respond to information in contralesional space. The dominant framework to explain these effects suggests that prisms influence higher order visuospatial processes by acting on brain circuits controlling spatial attention and perception. However, studies that have directly examined the influence of prisms on perceptual biases inherent to neglect have revealed very few beneficial effects. We propose an alternative explanation whereby many of the beneficial effects of prisms arise via the influence of adaptation on circuits in the dorsal visual stream controlling attention and visuomotor behaviours and suggest that prisms have little influence on the pervasive perceptual biases that characterize neglect.
Keywords: visual neglect; prism adaptation